The impact of board characteristics on earnings quality based on shareholder activism: Evidence from Chinese GEM listed companies - Wang, Yajie (2022)
This study seeks to observe the impact of the characteristics of the board members of Chinese GEM firms on their earnings quality and how this impact changes when moderated by shareholder activism. Data was collected from 720 companies in the Csmar database between 2009 and 2017. Then, a modified Jones model was used to calculate manipulable accrued profits as a proxy for earnings quality. The study examined five attributes of board members: gender, age, level of education, academic experiences, overseas experiences, and active shareholder role. The results of this research revealed an essentially positive relationship between these attributes of board members and earnings quality when considered on their own. In contrast, the influence of positive shareholder behaviour reduces the positive effect of board members characteristics on earnings quality.